Factors influencing the consequences of failure of sewer pipes - Wijas, Katarzyna (Instal, 2023)
The article presents the results of a survey conducted among Polish experts from the water and sewage industry. The aim of the analysis was to determine what factors and to what extent should be taken into account in assessing the consequences of structural and operational failures of sewers. Average weights were established for 15 factors, distinguishing between the above-mentioned types of failures. They were ranked from the most to the least important according to the opinion of the respondents. It was indicated which factors, according to experts, have no impact on the consequences of failure of sewer pipes.
Keywords: consequences of failure; structural failure; operational failure; risk of failure; sewers